Decreased occipital alpha oscillation in children who stutter during a visual Go/Nogo task. Issue 9 (September 2018) - Piispala, Johanna; Starck, Tuomo; Jansson-Verkasalo, Eira; Kallio, Mika
Highlights: Children who stutter (CWS) exhibit less alpha activity than controls during a visual Go/Nogo task. Controls had clear occipital alpha between stimuli while CWS showed a shift to slower frequencies. CWS show atypical function of attentional gating possibly due to immaturity of the brain networks. Abstract: Objective: Our goal was to discover attention- and inhibitory control-related differences in the main oscillations of the brain of children who stutter (CWS) compared to typically developed children (TDC). Methods: We performed a time-frequency analysis using wavelets, fast Fourier transformation (FFT) and the Alpha/Theta power ratio of EEG data collected during a visual Go/Nogo task in 7–9 year old CWS and TDC, including also the time window between consecutive tasks. Results: CWS showed significantly reduced occipital alpha power and Alpha/Theta ratio in the "resting" or preparatory period between visual stimuli especially in the Nogo condition. Conclusions: The CWS demonstrate reduced inhibition of the visual cortex and information processing in the absence of visual stimuli, which may be related to problems in attentional gating. Significance: Occipital alpha oscillation is elementary in the control and inhibition of visual attention and the lack of occipital alpha modulation indicate fundamental differences in the regulation of visual information processing in CWS. Our findings support the view of stuttering as part of a wide-ranging brain dysfunction most likely involving also attentional and inhibitory networks.